GAYA KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI PROFESIONAL GURU - anis fitriani (UNISAN JURNAL, 2024)
Leadership is sometimes defined as the exercise of authority and decision making. Becoming a professional teacher is a necessity. The teaching profession is also closely linked to integrity and personality, even synonymous with the image of humanity. Teacher professionalism will not exist or run smoothly without the efforts made by the school principal, because one of the ways teachers can become professional teachers is through the efforts made by the school principal in order to improve teacher quality. School principals should try to ask and approach teachers personally what and how many obstacles teachers face in completing their duties, both administratively and in the teaching and learning process. Training activities (Diklat) need to be carried out by teachers followed by follow-up efforts to implement the results of the training. Next is the implementation of special coaching programs such as certification. In certification, it is reflected that there is a fit and proper test that a teacher must undergo, against criteria that have ideally been determined. Keywords: Leadership Style, Professionalism Competence